Artificial Intelligence Basics : a Self-Teaching Introduction - Gupta, Neeru; Mangla, Ramita (Mercury Learning & Information, 2020)
"Designed as a self-teaching introduction to the fundamental concepts of artificial intelligence, the book begins with its history, the Turing test, and early applications. Later chapters cover the basics of searching, game playing, and knowledge representation. Expert systems and machine learning are covered in detail, followed by separate programming chapters on Prolog and Python. The concluding chapter on artificial intelligence machines and robotics is comprehensive with numerous modern applications. Features: Covers an introduction to concepts related to AI, including searching processes, knowledge representation machine learning, expert systems, programming, and robotics Includes separate chapters on Prolog and Python to introduce basic programming techniques in AI" -- publisher description.
Keywords: Artificial intelligence.; Electronic data processing.; elektronické knihy; electronic books